2017
DOI: 10.1016/j.bej.2017.03.018
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sludge retention time on mixed culture microbial fuel cell start-ups

Abstract: In this work, the start-ups of air-cathode microbial fuel cells (MFCs) seeds with conventional activated sludge cultivated at different solid retention times (SRTs) are compared. A clear influence of the SRT of the inoculum was observed, corresponding to an SRT of 10 days to the higher current density exerted, about 0.2 A m -2 . This observation points out that, in this type of electrochemical device, it is recommended to use high SRT seeds. The work also points out that in order to promote an efficient start-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Previous researches reported that some of the simple liquid substrates tested for MFCs application were such as solution with glucose (Chaudhuri and Lovley, 2003), volatile fatty acid (Daghio et al, 2015) and alcohol (Kim et al, 2007) and the common type of the complex mixture used as the feed sample for the MFC system were such as domestic wastewater (Chen et al, 2008;Dong et al, 2012;Liu et al, 2010), swine wastewater (Ding et al, 2017), agro food wastewater (Cecconet et al, 2017), artificial wastewater (He et al, 2005), synthetic wastewater (Mateo et al, 2017;Nam et al, 2010;Nandy et al, 2015), fruit processing wastewater (Abourached et al, 2016), tannery wastewater (Sawasdee and Pisutpaisal, 2016), brewery wastewater (Lu et al, 2017) and etc. MFCs application has also been tested to landfill leachate (Hassan et al, 2018).…”
Section: Mfc In Treating Spent Caustic Wastewatermentioning
confidence: 99%
“…Previous researches reported that some of the simple liquid substrates tested for MFCs application were such as solution with glucose (Chaudhuri and Lovley, 2003), volatile fatty acid (Daghio et al, 2015) and alcohol (Kim et al, 2007) and the common type of the complex mixture used as the feed sample for the MFC system were such as domestic wastewater (Chen et al, 2008;Dong et al, 2012;Liu et al, 2010), swine wastewater (Ding et al, 2017), agro food wastewater (Cecconet et al, 2017), artificial wastewater (He et al, 2005), synthetic wastewater (Mateo et al, 2017;Nam et al, 2010;Nandy et al, 2015), fruit processing wastewater (Abourached et al, 2016), tannery wastewater (Sawasdee and Pisutpaisal, 2016), brewery wastewater (Lu et al, 2017) and etc. MFCs application has also been tested to landfill leachate (Hassan et al, 2018).…”
Section: Mfc In Treating Spent Caustic Wastewatermentioning
confidence: 99%
“…With regard to the electrochemical performance, it must be stated that the operational conditions maintained during the process influence the steady-state power density exerted by an MFC [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…The literature has described the influence of the main parameters affecting the performance of a MFC. These parameters include the design and configuration of the MFC, the external resistance, inoculation, carbon source, operational temperature, loading rate and sludge age . Usually, high performance is linked to high coulombic efficiencies (CE), high surface to volume (S/V) ratio and low internal resistances .…”
Section: Introductionmentioning
confidence: 99%